Epidemiology, management, and outcomes of sepsis in ICUs among countries of differing national wealth across Asia - Li, Andrew; Ling, Lowell; Qin, Hanyu; M. Arabi, Yaseen; Myatra, Sheila Nainan; Egi, Moritoki; Kim, Hye Kyong; Mat Nor, Mohd Basri; Son, Do Ngoc (the American Thoracic Society, 2022)
Rationale: Directly comparative data on sepsis epidemiology and sepsis bundle implementation in countries of differing national wealth remain sparse. Objectives: To evaluate across countries/regions of differing income status in Asia 1) the prevalence, causes, and outcomes of sepsis as a reason for ICU admission and 2) sepsis bundle (antibiotic administration, blood culture, and lactate measurement) compliance and its association with hospital mortality. Methods: A prospective point prevalence study was conducted among 386 adult ICUs from 22 Asian countries/regions. Adult ICU participants admitted for sepsis on four separate days (representing the seasons of 2019) were recruited. Measurements and Main Results: The overall prevalence of sepsis in ICUs was 22.4% (20.9%, 24.5%, and 21.3% in low- income countries/regions [LICs]/lower middle-income countries/ regions [LMICs], upper middle-income countries/regions, and high-income countries/regions [HICs], respectively; P , 0.001). Patients were younger and had lower severity of illness in LICs/ LMICs. Hospital mortality was 32.6% and marginally significantly higher in LICs/LMICs than HICs on multivariable generalized mixed model analysis (adjusted odds ratio, 1.84; 95% confidence interval, 1.00–3.37; P = 0.049). Sepsis bundle compliance was 21.5% at 1 hour (26.0%, 22.1%, and 16.2% in LICs/LMICs, upper middle-income countries/regions, and HICs, respectively; P , 0.001) and 36.6% at 3 hours (39.3%, 32.8%, and 38.5%, respectively; P = 0.001). Delaying antibiotic administration beyond 3 hours was the only element independently associated with increased mortality (adjusted odds ratio, 2.53; 95% confidence interval, 2.07–3.08; P , 0.001). Conclusions: Sepsis is a common cause of admission to Asian ICUs. Mortality remains high and is higher in LICs/LMICs after controlling for confounders. Sepsis bundle compliance remains low. Delaying antibiotic administration beyond 3 hours from diagnosis is associated with increased mortality.